Abnormal Glucose Metabolism in Hispanic Parents of Children with Acanthosis Nigricans. (25th December 2011) - Urrutia-Rojas, Ximena; McConathy, Walter; Willis, Benjamin; Menchaca, John; Luna-Hollen, Mary; Marshall, Khiya; Lacko, Andras; Spellman, Craig
Abstract : Objective . Assess the prevalence of abnormal glucose metabolism among Hispanic parents of children with acanthosis nigricans (AN). Methods . Hispanic families( n = 258 ) were evaluated for metabolic and anthropometric parameters including fasting glucose levels and AN status. Results . Mothers with AN+ children had IFG (17.3%) and 4% had glucose levels ≥126 mg/dL( P = 0.028 ) compared to 7.1% and 1.8% of mothers with AN− children, respectively. Mothers of AN+ children also had greater odds of having impaired fasting glucose levels (OR: 3.917, 95% CI: 1.475–10.404;P < 0.004 ) but this was not the case for fathers (OR: 1.125, 95% CI: 0.489–2.586;P = 0.781 ). Mothers of AN+ children were also more likely to be AN+ (OR: 5.76, 95% CI: 2.98–11.13, P < 0.001 ). Screening discovered glucose levels >126 mg/dL in 9% of fathers with AN+ children. Conclusions . Hispanic mothers of AN+ children are at higher risk of carbohydrate metabolism abnormalities. AN in children can be a marker for prevention and delay programs aimed at identifying adults at risk for diabetes.